Abnormal methylation of Mill1 gene regulates osteogenic differentiation involved in various phenotypes of skeletal fluorosis in rats and methionine intervention - Niannian Chen; Jing Zhang; Congyu Yin; Yudan Liao; Lei Song; Ting Hu; Xueli Pan (Ecotoxicology and Environmental Safety)
Excessive fluoride intake can lead to skeletal fluorosis. Nutritional differences in the same fluoride-exposed environment result in osteosclerosis, osteoporosis, and osteomalacia. DNA methylation has been found to be involved in skeletal fluorosis and is influenced by environment and nutrition. In a previous study, we screened eight genes with differential methylation associated with various phenotypes of skeletal fluorosis. By combining gene functions, Mill1 gene was selected for subsequent experiments. First, we found that the Mill1 gene was hypomethylated and upregulated in osteosclerosis skeletal fluorosis, whereas it was hypermethylated and downregulated in osteoporosis/osteomalacia skeletal fluorosis. Similar results were obtained in the cell experiments. Subsequently, we validated the regulation of Mill1 gene methylation using DNMT1 and TET2 enzyme inhibitors. Furthermore, we knockdown and overexpression experiments confirmed its downregulation inhibited osteogenic differentiation, whereas osteogenic differentiation was promoted by its overexpression. These findings imply that abnormal methylation of the Mill1 gene triggered by fluoride under diverse nutritional conditions, regulates its expression and participates in osteogenic differentiation, potentially resulting in various phenotypes of skeletal fluorosis. Eventually, we use methionine for interventions both in vivo and in vitro. The results indicated that under normal nutrition and fluoride exposure followed by methionine intervention, the methylation levels of the Mill1 gene increased, whereas its high expression and enhanced osteogenic differentiation were restrained. This study offers a theoretical foundation for understanding the mechanism behind the various phenotypes of skeletal fluorosis through the perspective of DNA methylation and for employing nutrients to intervene in skeletal fluorosis.